PEMANFAATAN CANGKANG KELAPA SAWIT DALAM PEMBUATAN BRIKET DENGAN PENAMBAHAN PELEPAH KELAPA SAWIT - Wiranata, Leo Candra; Hamzah, Faizah; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Briquettes is one of the renewable energy alternatives that have uniformity of size, shape, density, and energy content. The purpose of this study was to examine the characteristics of briquettes consisting of a mixture of shells and midrib, and to determine the composition of the raw materials that can produce a briquettes with the best quality. The raw materials used were a mixture of shells and midrib with the proportion of 90%:10%, 80%: 20%%, 70%: 30%, 60%: 40%, and 50%: 50%. Types of tests performed on briquettes include crushing strength, moisture content, volatile matter, ash content, carbon bonded, and calorific value. The results of the tests showed briquettes crushing strength 3,54-6,07 kg/cm2, moisture content 3,24-4,14%, volatile matter 11,55-16,61%, ash content 4,94-5,23%, carbon bonded 74,01-80,25%, and calorific value 4181,04-6122,40 kal/g. The best quality of biopelet was in the percentage of shells and fronds was 80%: 20%.Keywords: Briquettes, palm shell, palm midrib, renewable energy